4‐2: Distinguished Student Paper: High Efficiency Color‐Converted Micro‐LED Displays. Issue 1 (29th May 2019) - Gou, Fangwang; Hsiang, En-Lin; Tan, Guanjun; Lan, Yi-Fen; Tsai, Cheng-Yeh; Wu, Shin-Tson
Abstract : With funnel‐tube array, the optical efficiency of the color‐converted micro‐LED display is improved by ~3X, while the crosstalk is eliminated. After optimization of the taper angle, the ambient contrast ratio is also improved due to higher light intensity.